Tutorials of Visual Graphic Communication Programs for Interior Design, Volume 2 - Cho, Yongyeon (Open textbook library., 2022)
This book is for advanced-level architecture and interior design students who have in-depth knowledge and skills with computer-aided visualization software. The author developed a total of twenty-two chapters to teach practical graphic presentation techniques for architectural presentations. Readers will learn these techniques by following step-by-step tutorials. This book includes multiple exercises for the reader's practice. After completing the tutorials, readers will be able to apply these techniques to their design projects.